Effects of total mixed ration with different levels of Lupinus angustifolius L. on growth performance and meat quality of male boer goats - Mohd Yusof, Ainul Yuzairi (2018)
As one of the major critical success factors in goat production, feed cost and its management have been given attention today to improve efficiencies and productivity of goat production. Total mixed ration (TMR) is an effective way of feeding goats by delivering a complete and nutritionally balanced diet for growing goats in intensive production system. Lupin grain (lupin) has high protein and dietary fiber content with minimal starch and glycemic index. Therefore, it has the potential as an alternative feed ingredient for livestock. However, the comparative data on the performances of Boer goat as affected by giving TMR with different level of lupin are still unavailable. Hence, present study was conducted to evaluate the effects of TMR diets with different lupin inclusion on the growth performance, carcass characteristics and meat quality traits of Boer goat. Twenty-four Boer male goats, 8-9-month-old of 27.83 ± 0.52 kg live body weight were allotted randomly into three treatment groups, namely CON, TMR A and TMR B, of eight animals each. Total mixed ration (TMR) feeds were formulated at 0%, 10% and 30% of lupin inclusion for CON, TMR A and TMR B groups, respectively. The TMR feeds were adjusted to be isocaloric (metabolizable energy: 10.3MJ/kg) and isonitrogenous (crude protein: 16.3%). The animals were fed twice (9.30am and 2.30pm) daily ad libitum during the 103-day feeding trial. All animals were humanely slaughtered according to the Halal slaughtering procedure at the end of the feeding trial. Present study showed that the total feed intake of TMR B (110.76 ± 3.57 kg) animals were significantly lower (P<0.05) than those in CON (135.05 ± 5.04 kg) and TMR A (125.07 ± 3.60 kg) groups. However, the final live weight, weight gained, and feed conversion ratio of the animals were unaffected (P>0.05) by the experimental diets. In addition, experimental diets also did not affect (P>0.05) the blood chemical content, carcass characteristics and composition of the Boer goats. In this study, the intramuscular fat in the longissimus dorsi (LD) muscle of TMR B (13.24 ± 1.28%) was lower (P<0.05) than that of CON (21.05 ± 1.49%) and TMR A (19.63 ± 1.53%). There was insignificant difference (P>0.05) in the other meat quality traits of the LD muscle among the experimental diets. Meanwhile, the fatty acid composition of LD, biceps branchii (BB) and semitendinosus (ST) muscles were affected by the experimental diets. In LD muscle, the proportions of lauric (C12:0), palmitoleic (C16:1) and linolenic (C18:3n-3) acids were significantly affected (P<0.05) by the experimental diets. Whilst, the proportion of pentadecanoic acid was significantly lower (P<0.05) in CON than that of TMR A in BB muscle. In ST muscle, TMR B had higher (P<0.05) proportion of lauric acid than CON, while the proportion of heptadecanoic acid was higher (P<0.05) in TMR A than that in TMR B. The total saturated fatty acid (SFA), monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) as well as the PUFA: SFA and n-6: n-3 ratios in all the three skeletal muscles were unaffected (P>0.05) by the experimental diets. Present findings demonstrated that feeding TMR diets with the up to 30% inclusion of lupin did not adversely affect the growth performance, carcass characteristics and meat quality of Boer goats. Hence, this finding suggested that TMR feeding with up to 30% of lupin inclusion is suitable for intensive farming of goats and serve as an alternative protein source to the animals.